PENGELOLAAN WAKTU DALAM PELAKSANAAN PENDIDIKAN ISLAM - Sabri, Ahmad (AT-TALIM, 2012)
Time does not become human beingsâ barrier to create and perform a variety of activities that give positive for them and society as long as they are able to manage it to be effective and efficient. It signaled that to achieve a lot of success in any jobs is determined how far a person is able to allocate the time and make a priority for their job. For general and Islamic educations in particular, the time management is also an important part of success in the educational activity. This sign has found in the Al-qurâan and the traditions of the Prophet Muhammad who emphasized the importance of time management, even in the Al-Qurâan, there is one verse that deliberately the importance of time (see Surah Al-âAhsr).